The Genetic Landscape of Fiber Flax - Duk, Maria; Kanapin, Alexander; Rozhmina, Tatyana; Bankin, Mikhail; Surkova, Svetlana; Samsonova, Anastasia; Samsonova, Maria (Frontiers in Plant Science, 2021)
Genetic diversity in a breeding program is essential to overcome modern day environmental challenges faced by the humanity and produce robust, resilient crop cultivars with improved agronomic characteristics, as well as to trace crop domestication history. Flax (Linum usitatissimum), one of the first crops domesticated by mankind, has been traditionally cultivated for fiber as well as for medicinal purposes and as nutritional product. The origins of fiber flax are hidden in the mists of time, and can be hypothetically traced back to either the Indo-Afghan region or Fertile Crescent. To shed new light into fiber flax genetic diversity and breeding history here we present a comprehensive analysis of the core collection of flax (306 accessions) of different morphotype and geographic origin maintained by the Russian Federal Research Center for Bast Fiber Crops. We observed significant population differentiation between oilseed and fiber morphotypes, as well as mapped genomic regions affected by recent breeding efforts. We also sought to unravel the origins of kryazhs, Russian heritage landraces, and their genetic relatedness to modern fiber flax cultivars. For the first time, our results provide strong genetic evidence in favor of hypothesis on kryazh’s mixed origin from both the Indio-Afghan diversity center and Fertile Crescent. Finally, we showed predominant contribution from Russian landraces and kryazhs into the ancestry of modern fiber flax varieties. Taken together, these findings may have practical implications on development of new improved flax varieties with desirable traits that give farmers greater choice in crop management and meet breeders aspirations.